G454(P) Retrospective survey of child protection case characteristics in an acute and community setting. (27th April 2015) - Sharma, R; Mistry, P
Abstract : Aim: The first principle of safeguarding services stated in the Munro report 2010 1 places the quality of experience and views of the child at the centre. Lord Laming's review in 2009 2 recommended minimum requirements to be met during the safeguarding process. Safeguarding assessments for children occur in both an outpatient (OP) clinic setting and in an acute out of hours (OOH) setting. The aim of this survey was to compare the number, type and outcome of safeguarding assessments between these two settings. Method: Retrospective case–notes review of all cases where a safeguarding examination was completed due to Section 47 concerns from January to March 2013. Those that were referred due to accidental incidents or where there was found to be no safeguarding concern were excluded. Data was obtained on documentation of the process and timeline for assessment as well as the types of case assessed. Outcomes one year later included children remaining with biological family and children remaining on a child protection plan. Results: A total of 67 safeguarding cases were seen during that period of time. 78% were seen in an OP setting. Median age =5 yrs 7 months (IQR 2 to 9 years). OOH median age = 20 months (IQR –12 to 35 months). Median waiting times and type of abuse were similar. Twenty eight percent were on a child protection plan (CPP) at the time of referral to the OP service versus 9% for OOH referrals. Fractures and burns were more often seen in the OOH setting whereas no injury seen was more often documented in the OP setting. Conclusions: The type of safeguarding cases seen do differ between acute and community settings in the age of presentation, the type of injury seen, the presence of history taking from the child and the numbers on a child protection plan at the point of referral. However the type of abuse, whether physical, neglect or sexual is similar. Further work needs to be done on standardising safeguarding practice across acute and community settings. References: The Munro Review of Child protection. Department of Education. 2011 The Protection of Children in England: A Progress Report. Department of Education. 2009